Efektifitas Konsumsi Bahan Bakar dan Kapasitas Perontokan Dengan Varian Berat Batang Padi - Yanto, Handi; Rizal, Yose; Aprizal, Aprizal (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
The rice thresher is very necessary in today’s agricultural mechanization process, to increase the productivity of agricultural products and speed up the time in post-harvest processing. The purpose of this study was to determine the capacity of the processed rice thresher machine, to determine the length of time required for one processing per cycle, and to determine the consumption of fuel used per cycle of testing. This research method uses an experimental method, namely by weighing the weight of the rice stalks before and after threshing. The results of this study were obtained, namely at a load of 1 kg of rice stalks it produced a capacity of 0.085 (kg/s) with the resulting fuel consumption of 0.21 (ml/s); a different load of 1.5 kg which produces a capacity of 0.098 (kg/hour) with a resulting fuel consumption of 0.25 (ml/s) and a load of 2 kg of rice stalks produces a capacity of 0.099 (kg/s) with a resulting fuel consumption of 0.27 (ml/s).